Molecular Identification of Three Stored Product Insect Species on Dried Fruits and Their Control with the Use of Some Aqueous Plant Extracts - Khidr, Sahand K.; Agha, Waran N.A.; Amin, Adil H. (Science Journal of University of Zakho, 2017)
Mortality of three insects; red flour beetle (Tribolium castaneum Herbst), khapra beetle (Trogoderma granarium Everts) and sawtoothed grain beetle (Oryzaephilus surinamensis (L.)) were evaluated via some aqueous plant extracts. The identification of three examined insects was carried out via designing specific primers for each aforementioned species with the use of PCR technique. The toxicity of aqueous plant extracts; eucalyptus (Eucalyptus camaldulensis Dehnh), mint (Mentha canadensis L.) and myrtle (Myrtus communis L.) at three dosages (12500, 25000 and 50000) ppm for 1, 2, 3 and 7 days were tested for their insecticidal activity against examined adults on dried fruits. Percentage mortality of insect was increased with an increase of doses and exposure times, whereas, not influenced significantly by the fruit types. T. castaneum was the most susceptible species, followed by T. granarium and O. surinamensis. Likewise, LC50 values were (3887.25, 10816.34 & 22763.48) on red flour, khapra & sawtoothed grain beetles respectively via using eucalyptus aqueous extract after 7 days on black raisin. While, higher doses required in order to kill fifty percentage of the population via myrtle aqueous extract and thus the LC50 values increased to (14726.86, 18421.43 & 39016.78) on the three aforementioned species respectively.
Keywords: Concentration; LC50; Dried Fruits; DNA Extraction; Mortality; Polymerase Chain Reaction